KESEJAJARAN BENTUK PENERJEMAHAN FRASA BAHASA ARAB DALAM CERAMAH HABIB UMAR BIN HAFIDZ - Hensa Utama, Muhammad Apridho; Masrukhi, Moh. (Arabi : Journal of Arabic Studies, 2022)
This study described the forms of Arabic phrases and the formal correspondence of Arabic phrases in Habib Umar bin Hafidz's lectures. This research is translational research using qualitative data and descriptive methods. The data source is the initial 13 minutes of the 47minutes video from the YouTube channel Al-Bahjah TV entitled " Pandangan Allah terhadap Hamba-Nya | Habib Umar bin Hafidz | Tausiyah Maulid Akbar HD (Malaysia)." The data is in Arabic phrases translated by Habib Ali Zainal Abidin. The findings of this study are that there are 28 Arabic phrases which are divided into five, namely five idhāfy phrases (nominal), six washfy phrases (adjectives), eight zharfy phrases (adverbial), four syibhul jumlah phrases (prepositions), and 5 ‘adady phrases (numerals). In addition, there are 13 parallel phrases, one phrase with a structural shift, nine phrases with a word-class shift, 2 with a unit shift, 2 with intra-system shifts, and one untranslated phrase.